Penilaian Keberlanjutan Padi Pada Tingkat Lahan Pertanian/Field Level Menggunakan Fuzzy Analytical Hierarchy Process (Fuzzy-Ahp - Anastasia Lidya Maukar; Johan Runtuk (Universitas Katolik Parahyangan, 2023)
Sustainable development in agriculture is needed to protect from economic, social and environmental aspects. The International Rice Research Institute has related goals, such as improving health by improving rice nutrition and food security and creating an environmentally friendly rice system. One of the United Nations’ sustainable development goals is to eliminate famine by implementing food security, improving nutrition, and encouraging agriculture sustainability. This study aims to identify the criteria, sub-criteria and assessment indicators and assess sustainable rice farming in two villages in Karawang, Parungsari and Pasirjengkol. The assessment consists of criteria, sub-criteria and indicators. Criteria and sub-criteria weights were also obtained from experts and calculated using the Fuzzy-Analytical Hierarchy Process (Fuzzy-AHP) method. Then, the rubric determines, and the assessment is carried out and compared to the standard. As a result, both regions have low score indicators. The results of the evaluation score for the economic, social and environmental criteria of Parungsari are 1,679; 2,615; and 3,495. The economic, social and environmental assessment scores of Pasirjengkol are 1,745; 2,588; and 3,189. Recommendations for improvement are also given for each low-scoring indicator.